Community Participation in the Planning and Preparation of the APBDes: An Analysis of Village Deliberation Practices in One Village in Medan City in the 2023-2024 Fiscal Year - Irza Faridz Muhammad; Dito Aditia Darma Nst (Journal of Management, Economic, and Accounting, 2026)
This study analyzes community participation in the planning and preparation of the APBDes in Suka Maju Village, Medan Denai District, Medan City, for the 2023-2024 period. With a qualitative approach, data was collected through in-depth interviews, field observations, short questionnaires, and APBDes documentation. The findings show that residents are actively proposing especially for infrastructure needs that have a direct impact; However, their influence on the composition of the final budget is incremental. Driving factors include pro-participatory leadership of village heads and local communication channels, while the main drivers are low budget literacy, less representative implementation times, limited access to detailed documents, and centralized decision-making practices. The analysis revealed that citizens' proposals tended to be recognized on the priority list, but technical verification, the drafting of the RAB, and the dynamics of informal lobbying determined the continuation of funding. The study recommends increasing citizens' budget literacy, training in RAB preparation for village officials, and strengthening document transparency to strengthen meaningful participation that has an impact on village expenditure allocation.